Federal Democratic Republic of Ethiopia : Options for Strengthening Land Administration - World Bank (World Bank, 2012)
Over the coming decades, land policy and administration, for urban as well as rural areas, will be critical for Ethiopia's development. The vast majority of people making up the Federal Democratic Republic of Ethiopia's (FDRE) predominantly agricultural economy live in rural areas. Finally, land policies and administration can contribute significantly to the objectives of promoting gender equality and protecting vulnerable groups in Ethiopia. This report aims to assist the government of Ethiopia in improving the performance of its land administration system based on a detailed review and lessons from Ethiopia and other countries. The three key areas for improvements and options for improving the land administration system summarized in the action matrix below are the: a) legal and regulatory framework; b) administrative capacity and organizational set-up; and, based on these, c) provision of efficient, cost-effective, and sustainable land administration services and land management.